Letter (copy) : Arrest of Constantino Perez Bratos - Citrine, Walter, 1887-1983
012a-0104-001 International WMC/WJB/AC/442 7th April, 1938. Mr.Charles Dukes, National Union of General & Municipal Workers, 5, Endsleigh Gardens, W.C.1 Dear Mr. Dukes, ARREST OF CONSTANTINO PEREZ BRATOS. I am returning herewith the letter about the case of Constantino Peres Bratos, for whom Lord Halifax promised yesterday to intervene with the authorities. I sent the particulars to him this morning by hand, and as soon as I receive any news, will at once communicate it to you. Yours faithfully, General Secretary. Letter from Public & Civil Services' International 292/946/12a/104